Analisis pengaruh produk domestik regional bruto, indeks pembangunan manusia, dan tingkat pengangguran terbuka terhadap tingkat kemiskinan di provinsi-provinsi sumatra - Hartina, Siti; Junaidi, Junaidi; Nurhayani, Nurhayani (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2024)
The objectives of this study are as follows: (1) To identify and analyze the development of Gross Regional Domestic Product, Human Development Index, and Open Unemployment Rate on poverty levels in Sumatra Provinces for the 2013-2018 period. (2) To analyze the influence of the growth of Gross Regional Domestic Product, Human Development Index, and Open Unemployment Rate on Poverty Levels in Sumatra Provinces for the 2013-2018 period. The data used in this research is secondary data obtained from the Central Statistics Agency (BPS), while the method used in this research is the panel regression analysis method with the REM method with the help of Eviews 9 software. The results of this study indicate that the gross regional domestic product variable has a negative and significant effect on the poverty level, the human development index variable has a significant negative effect on the poverty level, while the open unemployment rate has a significant positive effect on the poverty level.